Keanekaragaman Arthropoda pada Agroekosistem Sawah dengan Rekayasa Ekologi di Lahan Rawa Pasang Surut Banjar Kalimantan Selatan - Elisurya Ibrahim (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2020)
Ibrahim E. 2020. The diversity of arthropods in lowland agro-ecosystems with ecological engineering in tidal swamps of banjar, South Kalimantan. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-8 Tahun 2020, Palembang 20 Oktober 2020. pp. xx. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The diversity of arthropods has an important impact on the stability of the ecosystem. Arthropods in lowland agro-ecosystems consist of pests, natural enemies, and neutral insects that have their respective roles in the rice field ecosystem. To increase the type and number of arthropods, ecological engineering can be done in paddy fields by planting flowering plants. The purpose of this study was to determine the effect of ecological engineering on the diversity of rice field arthropods in tidal swamps . This research was conducted on tidal swamp rice type c in Guntung Ujung Village, Peat District, Banjar Regency, South Kalimantan from September - December 2017 using the observation method by observing periodically every week on 2 paddy fields, namely 1) Ecological Engineering Agroecosystem, using flowering plants (refugia) and pest control with andrometa which is a mixture of the entomopathogenic fungus Metharizium anisopliae and extract of sambiloto; 2) Conventional Agroecosystems, without flowering plants and pest control using pesticides. The results showed that the ecologically engineered rice field agroecosystem had a medium diversity index and species richness index, the number and types of predators and parasitoids in ecologically engineered rice fields was higher than conventional rice fields.